Circadian and temporal eating patterns in relation to metabolic syndrome in Iranian women - Azadeh Lesani; Mansooreh Sadat Mojani-Qomi (Scientific Reports)
Abstract Late energy intake (EI) is linked to increased obesity; however, the relationship between circadian eating patterns—including timing (morning vs. evening) energy and macronutrients, eating frequency, and eating window duration—and metabolic syndrome (MetS) in Iranian women remains insufficiently elucidated, particularly across age groups, menopausal statuses, and diurnal preference. In this cross-sectional study, dietary intake of 574 women aged 20 to 60 years from Tehran was assessed using three 24-hour dietary recalls. diurnal preference was evaluated through the Morningness-Eveningness Questionnaire. The analysis focused on eveningness in EI and macronutrient intake (%evening - %morning), eating occasions (EOs), and eating window duration. Anthropometric measurements, blood pressure, glucose, and lipid levels, were recorded. Generalized linear regression was utilized. Eveningness of EI was related to increased MetS risk T (tertile) 3 vs.T1 (ORs (95% CIs); 0.35 (0.11–0.62), p = 0.03). Also, the number of EOs T3 vs.T1 ( -0.68 (-1.32 – -0.23), p = 0.02) was related to decreased MetS. Eveningness of EI was linked to risk of elevated fasting blood glucose, T3 vs. T1 (0.46 (0.09–0.91), p = 0.02), Additionally, T3 vs. T1 in the Eveningness of protein showed a significant decrease in TG, (-0.56 (-1.01 - -0.12); p = 0.01). No associations were found in stratified by age, menopausal status, and chronotype. Consuming fewer meals along with a higher evening energy—might from non-protein sources—might be associated with increased the risk of MetS cross-sectionally, emphasizing the need for longitudinal studies to deepen our understanding of these relationships.